2021
DOI: 10.1007/s42399-021-00997-y
|View full text |Cite
|
Sign up to set email alerts
|

Modified National Early Warning Score as Early Predictor of Outcome in COVID-19 Pandemic

Abstract: COVID-19 represented an important challenge to the Italian healthcare system (IHCS). Our main aim was to obtain evidence to support the use of modified national early warning score (m-NEWS) as an interdisciplinary, common, and universal scoring scale to quickly recognize patients with a risk of clinical deterioration before admission and during hospitalization. As a secondary goal, we tried to find a score threshold that can trigger patients’ immediate medical review as a part of an optimal triaging protocol f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…As there has been widely shared disinformation on the social platforms during the pandemic, DHL of university students is affected when students cannot properly appraise the quality of information on COVID-19 and are manipulated by false information. The overabundance of COVID-19 related information could bring about negative mental health consequences to those who are not able to critically evaluate the information they read (37), as disinformation and fake news could lead to confusion and increased stress (38,39). As the Internet and digital platforms have become the major sources of health information regarding COVID-19, it is important to strengthen the DHL of students.…”
Section: Discussionmentioning
confidence: 99%
“…As there has been widely shared disinformation on the social platforms during the pandemic, DHL of university students is affected when students cannot properly appraise the quality of information on COVID-19 and are manipulated by false information. The overabundance of COVID-19 related information could bring about negative mental health consequences to those who are not able to critically evaluate the information they read (37), as disinformation and fake news could lead to confusion and increased stress (38,39). As the Internet and digital platforms have become the major sources of health information regarding COVID-19, it is important to strengthen the DHL of students.…”
Section: Discussionmentioning
confidence: 99%
“…El 10.2% (11) de los pacientes con clasificación de alto riesgo fallecieron; mientras que perecieron el 6.8% (5) y 4.9% (2) con clasificación de mediano y bajo riesgo respectivamente (Gráfico 2). El 25.9% (28) de los pacientes con puntuación de alto riesgo fue admitido en UCI, por otro lado, el 20.5% (15) riesgo mediano y el 17.1% (7) de riesgo bajo requirieron ingresar a UCI (Gráfico 3). Se realizó la prueba estadística no paramétrica correlación de Spearman, para analizar si existe asociación entre el puntaje obtenido con NEWS y el desenlace del paciente, obteniendo el coeficiente de correlación -0.08 IC 95% [-0.21;0.06] ῤ=0.25, así mismo; se buscó la correlación entre la estratificación de riesgo NEWS con el requerimiento de cuidados intensivos, siendo el coeficiente de correlación 0.08 IC 95% [0.05; 0.22] ῤ=0.21.…”
Section: Resultsunclassified
“…(14) La experiencia en China en el manejo del COVID -19, ha sugerido el uso de una versión modificada de NEWS (m -NEWS), asignando más puntaje cuando mayor es la edad del paciente, como ya se demostró en la literatura, esta es un factor de riesgo para la supervivencia. (15) Desarrollar una estrategia de puntuación ideal para pacientes con COVID -19, probablemente habría sido necesario también evaluar otros elementos epidemiológicos o fisiológicos. Los estudios con poblaciones relativamente pequeñas han obtenido resultados aparentemente controvertidos, el entorno de aplicación como en el contexto de pacientes agudos (emergencia, UCI) las características clínicas que definen mayor puntuación tienen posibles sesgos de medición (ejemplo: frecuencia respiratoria, temperatura, estado mental), las cuales dependen mucho del profesional de salud que realiza la toma de datos o variabilidad con el instrumento utilizado, como termómetros digitales.…”
Section: Discussionunclassified
“…This score already suggested in China for making triage decisions for patients with COVID-19 and we found the nearest cut-off value like them for predicting death [ 25 ]. The retrospective study performed in Alzano Lombardo hospital, Italy, indicated m-NEWS score 7 or greater at admission was associated with a negative outcome, which means patients need more intensive care and treatment, whereas patients who had m-NEWS score on admission under 7 were associated with a higher chance of recovery [ 6 ]. In the case of anticipating serious illness m-NEWS had less cut-off value, which is 4 or more might be the reason for excluding patients who had a serious illness during admission time as we want to prognosticate the patients who will get severe or critical COVID-19 later.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of patients with COVID-19 has created a burden on all tertiary level facilities [ 5 ]. In this complex situation, it became mandatory to develop systematic clinical strategies for efficient use of medical efforts to effectively treat COVID-19 and most importantly, identify a sub-population requiring immediate critical care to reduce fatal consequences [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%